2011
DOI: 10.1128/aac.00067-11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Allometric Scaling of Chloroquine in a Murine Malaria Model

Abstract: Chloroquine (CQ) is an important antimalarial drug for the treatment of special patient groups and as a comparator for preclinical testing of new drugs. Pharmacokinetic data for CQ in animal models are limited; thus, we conducted a three-part investigation, comprising (i) pharmacodynamic studies of CQ and CQ plus dihydroartemisinin (DHA) in Plasmodium berghei-infected mice, (ii) pharmacokinetic studies of CQ in healthy and malaria-infected mice, and (iii) interspecies allometric scaling for CQ from 6 animal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 66 publications
8
55
0
Order By: Relevance
“…Our analyses showed that the 95% CI encompassed both 2/3 and 3/4 for CL of artemether and artemisinin, whereas the upper limit of the 95% CIs for mefloquine, quinine, and chloroquine (0.63, based on reanalysis of a previous study [33]) were all Ͻ0.65 (Table 1). In contrast, the allometric exponents for dihydroartemisinin and piperaquine CL were 0.85 and 0.96, respectively, and the 95% CI of the exponent spanned unity.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Our analyses showed that the 95% CI encompassed both 2/3 and 3/4 for CL of artemether and artemisinin, whereas the upper limit of the 95% CIs for mefloquine, quinine, and chloroquine (0.63, based on reanalysis of a previous study [33]) were all Ͻ0.65 (Table 1). In contrast, the allometric exponents for dihydroartemisinin and piperaquine CL were 0.85 and 0.96, respectively, and the 95% CI of the exponent spanned unity.…”
Section: Discussionmentioning
confidence: 88%
“…Notwithstanding the limitations of interspecies scaling and the power law relationship debate, allometric scaling data indicate that fixed exponents of 2/3 or 3/4 may not be universally applicable in pharmacokinetics (24,28,29,31,33,38,44,47). Our analyses showed that the 95% CI encompassed both 2/3 and 3/4 for CL of artemether and artemisinin, whereas the upper limit of the 95% CIs for mefloquine, quinine, and chloroquine (0.63, based on reanalysis of a previous study [33]) were all Ͻ0.65 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the effects of CQ on the antimalarial immune response, we utilized a single dose of CQ that was not adequate to cure the infection and used it in Py 17XL-infected DBA2 mice, who can ordinarily clear the infection without exogenous treatment (Moore et al 2011). CQ was given to the mice at six hours p.i.…”
Section: Cq Treatment Influences the Infection Course In Dba/2 Mice Imentioning
confidence: 99%